EVALUATION OF ANTIBACTERIAL, ANTIFUNGAL AND ANTIOXIDANT POTENTIAL OF ESSENTIAL OIL FROM AMYRIS BALSAMIFERA AGAINST MULTI DRUG RESISTANT CLINICAL ISOLATES - Dahiya, Praveen; Manglik, Akshi (Asian Journal of Pharmaceutical and Clinical Research, 2013)
Objective: To investigate the phytochemical constituents, TLC bioautography and antioxidants of Amyris balsamifera essential oil. The antimicrobial potential was also determined against various multi drug resistant clinical isolates. Methods: Preliminary phytochemical analysis was performed. The antimicrobial potential of essential oil from Amyris was evaluated by agar well diffusion method against multi drug resistant clinical isolates. The antibacterial effect was investigated using the TLC-bioautographic method. The antioxidants analyzed include catalase, peroxidase, superoxide dismutase, glutathione-S-transferase and glutathione reductase. Results: Phytoconstituents analysis demonstrated the presence of few phytochemicals present including saponins, terpenoids and phlobatanins. Amyris balsamifera essential oil was further investigated for its antimicrobial activity against twelve Multi drug resistant pathogenic bacteria and three fungi respectively. The oil showed broad antimicrobial activity against MDR Gram-positive bacteria and Gram-negative bacteria and fungal isolates such as Staphylococcus aureus, Salmonella paratyphi, Escherichia coli, Klebsiella pneumoniae and Candida albicans. The highest in vitro inhibitory activity was observed for Klebsiella pneumoniae with wide inhibition zone diameters (20Â±0.11 mm) followed by Staphylococcus aureus (18Â±0.15) mm. Among fungal isolates, the growth of only Candida albicans was inhibited. Thin layer chromatography bioautography assay demonstrated one large growth inhibition zone observed at Rf values of 0.63 against Klebsiella pneumoniae and Staphylococcus aureus 1. Amyris balsamifera essential oil was found to be rich in antioxidants such as superoxide dismutase, glutathione-S-transferase and glutathione reductase. Conclusions: It can be concluded that, Amyris essential oil with good antimicrobial activity against several multi drug resistant clinical isolates and possessing antioxidant activity, thus can be used in the treatment of various microbial infections. Â Keywords: Antibacterial activity; Antifungal activity; Antioxidant potential; Amyris balsamifera; TLC bioautography